Validation of Designbuilder Simulation Accuracy Using Field Measured Data of Indoor Air Temperature in a Classroom Building - Abba, Habu Yusuf; Majid, Roshida Abdul; Ahmed, Muhammad Hamdan; Gbenga, Olutobi (Management, 2022)
KerkoCite.ItemAlsoKnownAs: 2129771:4UHQEB9X 4682641:55AFYSVG 5072953:WM5Q6W8Y
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; ⛔ No DOI found

An investigation of thermal comfort in classrooms in the tropical Savanna climate - Mustapha, Tajudeen Dele; Hassan, Ahmad Sanusi; Nasir, Muhammad Hafeez Abdul; Onubi, Hilary Omatule (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2022)
Studying the thermal environment in classrooms is essential due to its impact on students' health, teaching, learning, and productivity. In the Nigerian context, there is a general lack of thermal comfort studies, and none specifically relate to secondary school settings. This study aims to investigate students' perceptions of the indoor thermal environment and to determine the optimum temperature in naturally ventilated classrooms in the tropical savanna climate. Field investigations were conducted in free-running classrooms in Abuja to evaluate occupants' thermal comfort and perceptions. The study involves 901 pupils from 21 classrooms. Data were obtained through physical measurements of thermal comfort variables and a questionnaire survey on occupants' perceptions of the indoor thermal environment. The objective assessment indicated that 86% of the classrooms were inconsistent with the ASHRAE standard–55. Although 60% of the pupils were satisfied with their thermal environment, 78% preferred a cooler than neutral temperature. The result revealed a comfort temperature of 28.9 oC. The results extend the literature on thermal comfort in classrooms to the tropical savannah climate of the west African sub-region, which has received little attention in earlier research. The findings provide foundation data for developing a comfort standard for classrooms in the zone.
Number: 1 openalex:W4313580688.json KerkoCite.ItemAlsoKnownAs: 2129771:SCM2XDX6 2129771:SCM2XDX6 2129771:SCM2XDX6 2129771:SCM2XDX6 10.37934/araset.29.1.6275 4874017:X7YWDRM9 5072953:FV66BCLI 5072953:KS9NTX56
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:thermal comfort; oa:keyword:tropical savanna climate; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T12950 Learning Environments in Education; thermal sensation

Autoregressive neural networks with exogenous variables for indoor temperature prediction in buildings - Delcroix, Benoit; Ny, Jérôme Le; Bernier, Michel; Azam, Muhammad; Qu, Bingrui; Venne, Jean-Simon (Building Simulation, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:EGDEINDB
Keywords: _important; _z:class:countries; _z:class:themes; selected_for:Predictive models for classroom conditions 2024; ⛔ No DOI found